Canaloplasty with Stegmann Canal Expander for primary open‐angle glaucoma: two‐year clinical results. Issue 5 (13th January 2017) - Grieshaber, Matthias C.; Schoetzau, Andreas; Grieshaber, Hans R.; Stegmann, Robert
Abstract: Purpose: To examine longer‐term postsurgical safety and efficacy of a new expander for Schlemm's canal. Methods: In a non‐comparative, prospective study, 42 White patients with medically uncontrolled primary open‐angle glaucoma (POAG) underwent primary canaloplasty with >2‐year follow‐up. The bleb‐independent procedure comprised catheter‐assisted canaloplasty and implantation of two Stegmann Canal Expanders to maintain trabecular distension and canal patency over 180°. Intraocular pressure (IOP), glaucoma medication use and complications were assessed. Results: Mean IOP was 26.8 ± 5.6 mmHg presurgery, 12.8 ± 1.5 mmHg at 6 months, 13.2 ± 1.2 mmHg at 12 months and 13.3 ± 2.5 mmHg at 24 months (p < 0.001). Rate of complete success, defined as IOP ≤21, ≤18 and ≤16 mmHg and a ≥ 30% IOP reduction, was 85% (95% CI: 0.76–0.95), 85% (0.76–0.95) and 82% (0.70–0.96) at 12 months and 83% (0.73–0.94), 80% (0.70–0.92) and 80% (0.70–0.92) at 24 months. Preoperative factors were not significant predictors of ≤16 mmHg IOP reduction: IOP (hazard ratio [HR]: 0.68; 95% CI: 0.44–1.04; p = 0.08), mean visual defect (1.06; 0.90–1.20; p = 0.47), number of medications (0.59; 0.17–2.14; p = 0.42) and age (0.96; 0.87–1.13; p = 0.41). Number of medications dropped from 2.8 ± 0.4 presurgery to 0.2 ± 0.5 postsurgery (p < 0.001). Mean preoperative best‐corrected visual acuity was 0.19 ± SD 0.21 (range: 0–1.6), and logMAR was similar to 0.23 ± 0.16 (range: 0–1.6; p = 0.42) after a mean follow‐up of 27.4 months. Complications included peripheral Descemet's membrane detachment (7.2%) and trimming of the expander (4.7%) during surgery, and transient microhyphaema (23.8%) and IOP elevation (7.2%) postsurgery. Conclusion: Canaloplasty with the Stegmann Canal Expander was a safe and effective procedure to reduce IOP in White patients with moderate to advanced POAG.